2008
DOI: 10.1111/j.1365-3059.2008.01837.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and pathogenic variability in Ascochyta rabiei populations on chickpea in the Canadian prairies

Abstract: A population study of Ascochyta rabiei from the Canadian prairies was conducted to assess pathogenicity among isolates with the objectives to investigate the existence of a race or pathotype structure and to evaluate whether there had been a shift to higher aggressiveness between 1998 and 2002. Ninety‐nine isolates collected in 1998, 2001 and 2002 were inoculated onto seven differential chickpea genotypes. Significant isolate × differential interactions occurred, but accounted for a small proportion of the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…These varieties were considered partially resistant in North America in the early 1990s. The break-down of resistance in Sanford and CDC Xena most likely occurred because of the emergence of more aggressive isolates of A. rabiei (Vail and Banniza 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These varieties were considered partially resistant in North America in the early 1990s. The break-down of resistance in Sanford and CDC Xena most likely occurred because of the emergence of more aggressive isolates of A. rabiei (Vail and Banniza 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In A. rabiei of chickpea, a number of pathotypes were reported; for instance, more than ten pathotypes by Vir and Grewal, [32]; five pathotypes by Nene and Reddy, [1] and three pathotypes by Udupa et al [33]. Udupa et al [33] reported the occurrence of three pathotypes; pathotype I (less aggressive), pathotype II (aggressive) and pathotype III (most aggressive) as revealed by molecular markers [26,[34][35][36]. A new A. rabiei pathotype (pathotype IV) was reported in Syria that is capable of affecting the highly resistant chickpea genotypes (ICC-12004 and ICC-3996) known for their resistance to pathotypes I, II and III.…”
Section: Pathogen Variabilitymentioning
confidence: 99%
“…In pathosystems where resistance are quantitative (FlandezGalvez et al 2003), it is unlikely that isolates will group in discrete pathotypes (Caten 1987). The A. rabiei -C. arietinum pathosystem was thought to be based on a quantitative interaction (Gowen et al 1989;Vail and Banniza 2008), which suggested that a continuum of pathogenicity was more likely than true pathotypes. Although many other investigations have grouped isolates into pathotypes, in most cases few host genotypes have been used to differentiate them (Udupa et al 1998;Jamil et al 2000), and further investigation may find that the isolates tested did not represent the pathogen population.…”
Section: Discussionmentioning
confidence: 98%
“…Whether all of these groups are distinct pathotypes, or part of a continuum of aggressiveness within the population is unknown. Vail and Banniza (2008) were unable to categorise 99 isolates collected from the Canadian prairies into discrete pathotypes and concluded that there was a continuous distribution of pathogenicity.…”
Section: Introductionmentioning
confidence: 93%